Green Alternatives to Synthetic Acid–Base Indicators: A Quantitative Study of Apocynaceae Floral Extracts (Shaheed Smriti Journal, 2025)
This study evaluates floral extracts from the Apocynaceae family as sustainable alternatives to synthetic acid–base indicators. Flowers from Catharanthus roseus, Allamanda cathartica, Cascabela thevetia, Allamanda blanchetii, Catharanthus coriaceus, and Tabernaemontana divaricata were collected from Khairahani Municipality, Nepal, and analyzed for pigment composition. Anthocyanins, flavonoids, carotenoids, and alkaloids were identified, contributing to distinct pH-sensitive color changes. Comparative titration with synthetic indicators showed that Allamanda blanchetii and T. divaricata provided sharp, clear endpoints like phenolphthalein. The findings demonstrate that these plant-based indicators are biodegradable, non- toxic, cost-effective, and consistent with green chemistry principles, offering a viable alternative for analytical and educational applications while reducing environmental impact. This is the first reported study in Nepal assessing Apocynaceae species for analytical purposes.